Visualizing Atomically Layered Magnetism in CrSBr. Issue 27 (31st May 2022) - Rizzo, Daniel J.; McLeod, Alexander S.; Carnahan, Caitlin; Telford, Evan J.; Dismukes, Avalon H.; Wiscons, Ren A.; Dong, Yinan; Nuckolls, Colin; Dean, Cory R.; Pasupathy, Abhay N.; Roy, Xavier; Xiao, Di; et al.
Abstract: 2D materials can host long‐range magnetic order in the presence of underlying magnetic anisotropy. The ability to realize the full potential of 2D magnets necessitates systematic investigation of the role of individual atomic layers and nanoscale inhomogeneity (i.e., strain) on the emergence of stable magnetic phases. Here, spatially dependent magnetism in few‐layer CrSBr is revealed using magnetic force microscopy (MFM) and Monte Carlo‐based simulations. Nanoscale visualization of the magnetic sheet susceptibility is extracted from MFM data and force–distance curves, revealing a characteristic onset of both intra‐ and interlayer magnetic correlations as a function of temperature and layer‐thickness. These results demonstrate that the presence of a single uncompensated layer in odd‐layer terraces significantly reduces the stability of the low‐temperature antiferromagnetic (AFM) phase and gives rise to multiple coexisting magnetic ground states at temperatures close to the bulk Néel temperature ( T N ). Furthermore, the AFM phase can be reliably suppressed using modest fields (≈16 mT) from the MFM probe, behaving as a nanoscale magnetic switch. This prototypical study of few‐layer CrSBr demonstrates the critical role of layer parity on field‐tunable 2D magnetism and validates MFM for use in nanomagnetometry of 2D materials (despite the ubiquitous absence of bulk zero‐field magnetism in magnetized sheets). Abstract : CrSBr is a layered material possessing intralayer ferromagnetic and interlayer antiferromagnetic (AFM) ordering at low temperatures ( T  < 132 K). At higher temperatures or in the presence of modest magnetic fields, AFM correlations are suppressed, yielding a magnetic phase with a comparatively high sheet susceptibility (χ 2D ). Magnetic force microscopy is sensitive to χ 2D and identifies local nanoscale magnetic ordering.